Strategic inventory reduction of Company ABC - Carillo, Jeff Michael P.; Dalmacio, Aliya Luisa M.; Raagas, Christian Jay B.; Salvo, Jose Miguel R.
This study presents a method to decrease total inventory cost (presented in Days of Inventory or DOI) of Company ABC. The study focuses on decreasing DOI contributed by cycle stock and lead time. The optimal production interval of each product per week, which is used to determine DOI contribution of cycle stock, is recalculated so that it allows fractional production interval instead of always being rounded to the nearest whole number. Additionally, lead time stock is recalculated so that it considers destination of delivery and amount of orders to each depot that a certain product is being delivered. Limitations considered in this study include being constrained to the given data used and disregarding company policies that may automatically change the replenishment strategy of each product given the changes in segmentation code and production interval. Results showed that by correcting the calculation of cycle stock, there is a 2.7 DOI decrease, which is equivalent to a reduction of USD 13.78M in inventory cost. Consequently, recalculation of lead time stock resulted to a 0.4 DOI decrease, equivalent to a reduction of USD 2.04M in inventory cost, and adding this to the effect of cycle stock recalculation results to a total reduction of USD 15.82M in inventory cost.